Pilot brewery tests of Czech flavour hop varieties registered in 2022 - Mikyška, Alexandr; Slabý, Martin; Jurková, Marie; Štěrba, Karel; Nesvadba, Vladimír; Charvátová, Jitka (KVASNY PRUMYSL, 2022)
Seven new Czech “flavour hop” varieties were tested in pilot brewing trials (50 l), in which samples of Ale-style beer were prepared using dry hopping. Essential oils in the beer were determined by fluidized-bed extraction combined with gas chromatography–mass spectrometry. Hop-derived aromas in beer were evaluated by descriptive method. Comparison of terpene essential oils in samples showed differences between hop genotypes and only a partial relationship with the sensory profile of beer. A cluster analysis of hop aromas in beer revealed the relationship between the pairs of Saturn and Pluto; N and Eris; Ceres and Jupiter hop varieties. The submitted results present the sensory properties of these new varieties and are useful for further study of the relationship between chemical and sensory profile of dry hopped beers.